2020
DOI: 10.1002/cpdd.891
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vedolizumab Disease‐Drug‐Drug Interaction Potential in Patients With Inflammatory Bowel Diseases

Abstract: Disease‐drug‐drug interactions (DDDIs) have been identified in some inflammatory diseases in which elevated proinflammatory cytokines can downregulate the expression of cytochrome P450 (CYP) enzymes, potentially increasing systemic exposure to drugs metabolized by CYPs. Following anti‐inflammatory treatments, CYP expression may return to normal, resulting in reduced drug exposure and diminished clinical efficacy. Vedolizumab has a well‐established positive benefit‐risk profile in patients with ulcerative colit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 50 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…In this data set, baseline cytokine or 4β‐hydroxycholesterol levels (Tables S2 and S3 ) appeared to overlap with the ranges reported in healthy patients. 13 , 20 , 21 The only cytokine with evidence of transient (2.4‐fold) increase was IFN‐ɣ, which had decreased toward the baseline by 2 weeks after the dose. No modulation of any other inflammatory cytokines was observed with bintrafusp alfa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this data set, baseline cytokine or 4β‐hydroxycholesterol levels (Tables S2 and S3 ) appeared to overlap with the ranges reported in healthy patients. 13 , 20 , 21 The only cytokine with evidence of transient (2.4‐fold) increase was IFN‐ɣ, which had decreased toward the baseline by 2 weeks after the dose. No modulation of any other inflammatory cytokines was observed with bintrafusp alfa.…”
Section: Resultsmentioning
confidence: 99%
“…11 Studies of other therapeutic proteins have used profiling of proinflammatory cytokines to exclude potential perpetrator DDIs and eliminate the need for clinical DDI assessment. 12,13 Clinical safety data, together with population PK assessments, have indicated a low risk of victim DDI for bintrafusp alfa as monotherapy or in combination with chemotherapeutics, thus enabling the design of multiple combination phase II and III clinical trials NCT02517398, NCT04066491, and NCT03840915. 14,15 Bintrafusp alfa has a unique mechanism of action and is a direct cytokine modulator via neutralization of TGFβ.…”
Section: Introductionmentioning
confidence: 99%
“…In colon biopsy samples from patients with ulcerative colitis and patients with Crohn’s disease, a DNA microarray analysis has uncovered broad suppression of genes involved in drug metabolism; this dysregulation is accompanied by pronounced downregulation of PXR [ 418 ]. Some authors have compared serum levels of proinflammatory cytokines and pharmacokinetic parameters of drugs–substrates of CYP3A enzymes between healthy individuals and patients with ulcerative colitis or Crohn’s disease [ 419 , 420 ]; it has been demonstrated there that higher baseline serum levels of proinflammatory cytokines (TNF, IL-1β, IL-6, and IL-8) in the patients do not cause a change in CYP3A4 activity, as evidenced by the pharmacokinetic parameters of the drugs–substrates of CYP3A enzymes in such patients. Those researchers concluded that inflammatory bowel disease does not elevate the production of proinflammatory cytokines to the clinically significant levels that could alter pharmacokinetics of drugs–substrates of CYP3A enzymes [ 419 , 420 ].…”
Section: Cyp3a Involvement In Pathological Processesmentioning
confidence: 99%
“…Some authors have compared serum levels of proinflammatory cytokines and pharmacokinetic parameters of drugs–substrates of CYP3A enzymes between healthy individuals and patients with ulcerative colitis or Crohn’s disease [ 419 , 420 ]; it has been demonstrated there that higher baseline serum levels of proinflammatory cytokines (TNF, IL-1β, IL-6, and IL-8) in the patients do not cause a change in CYP3A4 activity, as evidenced by the pharmacokinetic parameters of the drugs–substrates of CYP3A enzymes in such patients. Those researchers concluded that inflammatory bowel disease does not elevate the production of proinflammatory cytokines to the clinically significant levels that could alter pharmacokinetics of drugs–substrates of CYP3A enzymes [ 419 , 420 ]. Nonetheless, examination of intestinal biopsy samples from people with and without Crohn’s disease and quantification of CYP3A4 expression by Western blotting indicate a significant decrease in protein expression of CYP3A4 in the ileum (by 45%) and colon (by 78%) in subjects with Crohn’s disease relative to subjects without it [ 421 ].…”
Section: Cyp3a Involvement In Pathological Processesmentioning
confidence: 99%
“…In one study, CYP3A4 activity was not modulated in patients with inflammatory bowel diseases treated with vedolizumab. 62…”
Section: T a B L E 3 Continuedmentioning
confidence: 99%